2020
DOI: 10.18499/2225-7357-2020-9-3-72-85
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms of central nervous system alteration in COVID-19

Abstract: The ongoing coronavirus disease 2019 (COVID-19) pandemic dictates the need to study the molecular and cellular mechanisms of interaction between the pathogen and the human body. The manifestation of neurological symptoms in some patients with COVID-19 is a problem for neuroscientists due to the insufficiently understood pathomorphogenesis of the disease. This review systematizes the literature data reflecting the ways of penetration of SARS-CoV-2 into the brain, features of its interaction with neurons, neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 95 publications
(194 reference statements)
0
2
0
Order By: Relevance
“…Two volunteers of the control group were identified who, according to the resource www.covid19diagnosis.ru, had been ill with COVID-19 about 12 and 18 months ago. Figures 3,4 and 5,6 show that the first conclusion from the results of this study was the understanding that in the early period after COVID-19, patients showed a significant decrease in baseline impedance during light exercise. The reason for this is most likely the massive suffering of the patency of the capillaries of the hemomicrocirculatory bed (HMCB) due to micro thrombosis caused by the new coronavirus infection SARS-CoV-2, which is confirmed by numerous pathological studies [18,19].…”
Section: Discussion Of Research Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Two volunteers of the control group were identified who, according to the resource www.covid19diagnosis.ru, had been ill with COVID-19 about 12 and 18 months ago. Figures 3,4 and 5,6 show that the first conclusion from the results of this study was the understanding that in the early period after COVID-19, patients showed a significant decrease in baseline impedance during light exercise. The reason for this is most likely the massive suffering of the patency of the capillaries of the hemomicrocirculatory bed (HMCB) due to micro thrombosis caused by the new coronavirus infection SARS-CoV-2, which is confirmed by numerous pathological studies [18,19].…”
Section: Discussion Of Research Resultsmentioning
confidence: 60%
“…The pathogenesis of the post-COVID syndrome is based on the systemic suffering of the hemomicrocirculatory bed of tissues and organs, triggered by the processes of thrombus formation due to a radical change in the hemorheological properties of blood [ 6 , 7 , 8 ]. And at present, there are no hardware or biochemical systems that make it possible to assess the severity of this process in vivo, only postmortem histological examination [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%